Notch4 Inhibition Suppresses Invasion and Vasculogenic Mimicry Formation of Hepatocellular Carcinoma Cells - 程锐;蔡欣然;柯坤;陈燕凌 (Current medical science, 2017)
Vasculogenic mimicry（VM） is a process by which aggressive tumor cells generate non-endothelial cell-lined channels in malignant tumors including hepatocellular carcinoma（HCC）. It has provided new insights into tumor behavior and has surfaced as a potential target for drug therapy. The molecular events underlying the process of VM formation are still poorly understood. In this study, we attempted to elucidate the relationship between Notch4 and VM formation in HCC. An effective si RNA lentiviral vector targeting Notch4 was constructed and transfected into Bel7402, a HCC cell line. VM networks were observed with a microscope in a 3 dimensional cell culture system. Cell migration and invasion were evaluated using wound healing and transwell assays. Matrix metalloproteinases（MMPs） activity was detected by gelatin zymography. Furthermore, the role of Notch4 inhibition in Bel7402 cells in vivo was examined in subcutaneous xenograft tumor model of mice. The results showed that downregulation of Notch4 destroyed VM network formation and inhibited migration and invasion of tumor cells in vitro（P〈0.05）. In vivo, tumor growth was also inhibited in subcutaneous xenograft model（P〈0.05）. The potential mechanisms might be related with down-regulation of MT1-MMP, MMP-2, MMP-9 expression and inhibition of the activation of MMP2 and MMP9. These results indicated that Notch4 may play an important role in VM formation and tumor invasion in HCC. Related molecular pathways may be used as novel therapeutic targets for HCC antiangiogenesis therapy.